PERLINDUNGAN HUKUM TERHADAP DEBITUR DALAM PENARIKAN SITA JAMINAN FIDUSIA TANPA MELALUI LELANG PENGADILAN - Anggi Purnama Tradesa; Zainal Asikin; Eduardus Bayo Sili (UNES Law Review, 2021)
Debtors as legal subjects are entitled to legal protection, both preventive and repressive, written or unwritten. The legal protection provided is an implementation of the principle of recognition and dignity that is rooted in Pancasila and the Constitution. This study aims to analyze the protection and legal remedies of the debtor in withdrawing the confiscation of fiduciary guarantees without going through a court auction. This research is a normative legal research. The results of this study include: The debtor's legal effort in withdrawing a fiduciary guarantee without going through a court auction is to ask the creditor to show a Fiduciary Guarantee Certificate issued by the Fiduciary Registration Office. If the creditor cannot show a fiduciary guarantee certificate, then the debtor does not need to submit the collateral, because the creditor does not have the right to execute the collateral.